Digital transformation in higher education for achieving sustainable development goals in conflict zones: a case study of An-Najah National University - Al-Shaer, NaserEddeen M.; Hattab, Muayad K.; Khlaif, Zuheir N.; Alsher, Tasnim Naser; Adas, Noor Omar; Al-Kilani, Jamal Ahmad; Fatayer, Osayd Sulayman; Khaled, Ghassan Shareef; Odeh, Mohammad Subhi; Bkheet, Emran Izzat (Frontiers in Human Dynamics, 2025)
Digital transformation (DT) is increasingly recognized as a vital strategy for advancing education and achieving the Sustainable Development Goals (SDGs). In conflict-affected regions, however, its implementation faces distinct challenges tied to political instability, financial constraints, and weak legal frameworks. This study explores how DT is being adopted in higher education through a case study of An-Najah National University (NNU) in Palestine. Using a qualitative design, data were collected through semi-structured interviews with senior decision-makers and DT specialists, supported by an analysis of institutional practices. Results show that DT tools have improved educational access, strengthened resilience, and enhanced administrative efficiency. Online and blended learning enabled students to continue their education despite checkpoints and closures, while digital correspondence reduced paperwork and streamlined communication. At the same time, significant barriers remain, including fragmented governance, limited infrastructure, and the absence of clear legal frameworks. The study concludes that DT can serve as a resilience mechanism in conflict-affected regions by enabling continuity and inclusivity in education, but its full potential depends on targeted policy reforms, capacity-building efforts, and stronger international partnerships. By situating the Palestinian experience within the broader context of fragile and resource-constrained regions, this research contributes practical insights for institutions worldwide that face similar challenges.